2004
DOI: 10.1074/jbc.m308954200
|View full text |Cite
|
Sign up to set email alerts
|

Site of Docking and Fusion of Insulin Secretory Granules in Live MIN6 β Cells Analyzed by TAT-conjugated Anti-syntaxin 1 Antibody and Total Internal Reflection Fluorescence Microscopy

Abstract: To determine the site of insulin exocytosis in the pancreatic ␤ cell plasma membrane, we analyzed the interaction between the docking/fusion of green fluorescent protein-tagged insulin granules and syntaxin 1 labeled by TAT-conjugated Cy3-labeled antibody (Ab) using total internal reflection fluorescence microscopy (TIRFM). Monoclonal Ab against syntaxin 1 was labeled with Cy3 then conjugated with the protein transduction domain of HIV-1 TAT. TAT-conjugated Cy3-labeled antisyntaxin 1 Ab was transduced rapidly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
106
2
8

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(125 citation statements)
references
References 34 publications
9
106
2
8
Order By: Relevance
“…This possibility is strongly supported by a very recent report that movements of insulin-containing dense-core secretory vesicles along the cortical actin network depend on myosin-Va and are essential for regulated exocytosis (Varadi et al, 2005). In addition, syntaxin-1 is localized close to the site of exocytosis (Stanley et al, 2003;Ohara-Imaizumi et al, 2004), where it could participate in the process of exocytosis by interacting with myosin-Va.…”
Section: Is the Interaction Between Myosin-va And Syntaxin-1a Physiolsupporting
confidence: 60%
See 1 more Smart Citation
“…This possibility is strongly supported by a very recent report that movements of insulin-containing dense-core secretory vesicles along the cortical actin network depend on myosin-Va and are essential for regulated exocytosis (Varadi et al, 2005). In addition, syntaxin-1 is localized close to the site of exocytosis (Stanley et al, 2003;Ohara-Imaizumi et al, 2004), where it could participate in the process of exocytosis by interacting with myosin-Va.…”
Section: Is the Interaction Between Myosin-va And Syntaxin-1a Physiolsupporting
confidence: 60%
“…This possibility is strongly supported by a very recent report that movements of insulin-containing dense-core secretory vesicles along the cortical actin network depend on myosin-Va and are essential for regulated exocytosis (Varadi et al, 2005). In addition, syntaxin-1 is localized close to the site of exocytosis (Stanley et al, 2003;Ohara-Imaizumi et al, 2004), where it could participate in the process of exocytosis by interacting with myosin-Va.A previous report indicated that hippocampal slices of dilute lethal mice, which lack myosin-Va, do not show a The anti-myosin-Va neck antibody does not alter myosin-Va-based sliding velocity. Velocity measurements were carried out as described in Figure 2D in the presence of 1:200 anti-myosin-Va neck antibody (bottom; n ϭ 80) or normal IgG (middle; n ϭ 66) at pCa ϭ 6.…”
supporting
confidence: 60%
“…Interestingly, this treatment had been reported to inhibit all types of regulated exocytosis investigated so far (Lang et al, 2001;Ohara-Imaizumi et al, 2004;Salaun et al, 2004). In PC12-27 cells, depletion was amply effective, as revealed by the blockade of the cholera toxin endocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…The functional equivalent of the presynaptic active sites of secretion in ␤ cells are microdomains (alternatively referred to as "excitosomes," "Ca 2ϩ microdomains," or "secretory microdomains"), where the submembrane secretory apparatus assembles beneath the plasma membrane in close proximity to voltage-gated calcium channels (43)(44)(45)(46). Because these microdomains seem to be especially important for early phase insulin secretion, we next asked whether NL-2 affected early phase insulin secretion more than late phase (47)(48)(49).…”
Section: Presence Of Nl-2 and Nl-2 Binding Partner On ␤ Cell Surface-mentioning
confidence: 99%